2013
DOI: 10.1039/c3nr34134h
|View full text |Cite
|
Sign up to set email alerts
|

A nanocrystalline Sm–Co compound for high-temperature permanent magnets

Abstract: The inherently high magnetic anisotropy and nanoscale grain size in a Sm5Co19 compound result in an intrinsic coercivity far higher than those of known Sm-Co compounds prior to orientation treatment. The combination of ultrahigh intrinsic coercivity, high Curie temperature and low coercivity temperature coefficient of nanocrystalline Sm5Co19 as a single phase material shows it to be a very promising compound to develop outstanding high-temperature permanent magnets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Sm-Co intermetallic compounds are known to be the best performing permanent magnets in a high temperature range. [1][2][3] Compared with the equilibrium phases Sm 2 Co 17 (2:17) and SmCo 5 (1:5), the metastable phase SmCo 7 (1:7) shows higher Curie temperature together with strong uniaxial magnetocrystalline anisotropy. 4 Thus, alloys with the stabilized 1:7 phase are the prime candidates for advanced permanent magnets that are to be applied in a high temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…Sm-Co intermetallic compounds are known to be the best performing permanent magnets in a high temperature range. [1][2][3] Compared with the equilibrium phases Sm 2 Co 17 (2:17) and SmCo 5 (1:5), the metastable phase SmCo 7 (1:7) shows higher Curie temperature together with strong uniaxial magnetocrystalline anisotropy. 4 Thus, alloys with the stabilized 1:7 phase are the prime candidates for advanced permanent magnets that are to be applied in a high temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…Metastable phases in the Sm-Co system, such as SmCo 7 , Sm 5 Co 19 and SmCo 9.8 , have been successfully prepared by some non-equilibrium techniques developed in recent years [47,61,62,82,83] . The metastable phase dominated alloys can have special and outstanding functional properties, which may be difficult to obtain in equilibrium phased alloys.…”
Section: Metastable Phasesmentioning
confidence: 99%
“…In this review, we provide an overview of modeling studies of phase stability in alloys, including theories, models and methods. The Sm-Co alloy system, as one of the two most famous rare-earth permanent magnetic materials families [45] , is taken as an example, with the consideration that this system is rich in various stable and metastable phases under the conditions of binary compositions [46][47][48][49][50][51][52][53] . Efforts are made to introduce the progress in the studies of the phase stability and transformation behavior of Sm-Cobased alloys, in which the development of the research approaches from the traditional CMS methods to strategies based on the materials informatics is particularly demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…either by altering the processing parameters or by the addition of some alloying element. According to Zhexu Zhang et al, 1) for a singlephase binary alloy of SmCo, by far the maximum coercivity is 36.76 kOe, which was achieved in case of Sm 5 Co 19 phase. Though, Lei Fang et al, 2) demonstrated that dry milling of SmCo5 yielded 41 kOe coercivity.…”
Section: Introductionmentioning
confidence: 99%